Impulse Buying Behavior of Generation Z Urban Muslims on Shopee - Auliaramadhan, Nathasyanaza; Asnawi, Haris Faulidi; Khaliq, Restu (Prodi Ekonomi Syariah Pascasarjana IAIN Kudus, 2024)
This study aims to analyze the effect of flash sales and free shipping taglines on impulse buying behavior among Generation Z urban Muslim users of the Shopee marketplace. The research design employs quantitative methods with a sample size of 97 Generation Z urban Muslim respondents in Banjarmasin City. The data analysis utilizes multiple linear regression. The results showed that flash sale significantly affects impulsive buying behavior, while the free shipping tagline has no significant effect. This study contributes to providing empirical evidence about the behavioral preferences of Generation Z urban Muslim consumers, especially impulse buying behavior in online shopping. In the context of marketing, e-commerce platforms must consider the distinctive characteristics of Generation Z urban Muslims when developing promotional strategies to boost sales.